Kampung Pancasila: Resolusi Konflik Keagamaan di Kwangenrejo: Kampung Pancasila: Religious Conflict Resolution in Kwangenrejo - Pancaningsih, Siti Samrotul; Sunesti, Yuyun; Zuber, Ahmad (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2024)
This article aims to analyze the implementation of the Pancasila Village in Kwangenrejo Village as a strategy for resolving religious conflicts. This study employs a qualitative approach, with informants selected through purposive sampling techniques. Data collection methods include in-depth interviews, participatory observation, and documentary studies. Data analysis adheres to the framework proposed by Miles, Huberman, and Saldana. The findings reveal that the transformation of Kwangenrejo into a Pancasila Village has successfully reduced tensions and promoted interfaith harmony. Activities such as the socialization of Pancasila values, installation of Pancasila stickers, and revitalization of the mutual assistance culture demonstrate the effectiveness of Pancasila values in resolving conflicts and fostering harmony. The study concludes that the implementation of the Pancasila Village in Kwangenrejo illustrates that the application of Pancasila values can serve as an effective strategy in religious conflict resolution. Abstrak Artikel ini bertujuan untuk menganalisis implementasi Kampung Pancasila di Kampung Kwangenrejo sebagai strategi resolusi konflik keagamaan. Kajian ini menggunakan pendekatan kualitatif, informan dipilih melalui teknik Purposive sampling dan teknik pengumpulan data menggunakan wawancara mendalam, pengamatan partisipatif, dan studi dokumentasi. Analisis data mengikuti kerangka kerja Miles, Huberman, dan Saldana. Kajian ini menunjukkan bahwa transformasi Kwangenrejo menjadi Kampung Pancasila berhasil mengurangi ketegangan dan mempromosikan kerukunan antaragama. Kegiatan seperti sosialisasi nilai-nilai Pancasila, pemasangan stiker Pancasila, dan revitalisasi budaya gotong royong menunjukkan efektivitas implementasi nilai Pancasila dalam menyelesaikan konflik dan membangun kerukunan. Kajian menyimpulkan bahwa implementasi Kampung Pancasila di Kwangenrejo menunjukkan bahwa penerapan nilai-nilai Pancasila dapat menjadi strategi efektif dalam resolusi konflik keagamaan.